Between seeing and acting: a dialogue on surveillance and behavioral modulation through the thought of Shoshana Zuboff - Silva, Francisca Galiléia Pereira da (Argumentos - Revista de Filosofia, 2025)
The present article aims to examine the relationship between the process of the algorithmization of life and the techno-epistemological infrastructure characteristic of what has been termed “surveillance capitalism”. To this end, it is understood as fundamental to analyze the transformation of human action into predictive raw material, a process that consolidates new forms of power that combine informational asymmetry, surveillance, and behavioral modulation. In this direction, a dialogue is established with thinkers of the informational revolution promoted by Information and Communication Technologies, taking as its central element the concept of surveillance capitalism developed by the philosopher Shoshana Zuboff.